Pengaruh Environmental, Social, Governance (ESG) Disclosure, dan Kinerja Keuangan Terhadap Return Saham - Rani Putri; Fiola Finomia Honesty; Helga Nuri Honesty (Komunitas Dosen Indonesia, 2024)
This study aims to examine the impact of environmental, social, and governance (ESG) disclosure and financial performance on stock returns. This research employs a quantitative approach. The research subjects are mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The sample was selected using purposive sampling. The research sample obtained was 96 for a four-year research period. The data analysis employed in this study is multiple linear regression, conducted using SPSS version 26. The results of this study indicate that Environmental disclosure, Social disclosure, Governcance disclosure and return on assets do not have a significant influence on stock returns. Earnings per share has a positive influence on stock returns. This research contributes to the advancement of knowledge and insights in the field of accounting, as well as the factors influencing stock returns in the mining sector.future research should expand population and sample sizes beyond mining sector companies. Utilizing comprehensive ESG databases (e.g., MSCI ESG Ratings, Sustainalytics) and analizing additional factors like industry growth and company size to moderate ESG – return relationships is recommended